2022
DOI: 10.3389/fpls.2022.917528
|View full text |Cite
|
Sign up to set email alerts
|

Responses of photosynthetic characteristics of oat flag leaf and spike to drought stress

Abstract: Raising crops production via improving photosynthesis has always been focused. Recently excavating and increasing the photosynthetic capacity of non-leaf organs becomes an important approach to crops yield increase. Here we studied the photosynthetic characteristics of the flag leaf and the non-leaf organs including the sheath, the glume and the lemma under greenhouse. The relative water content (RWC), the stomatal characteristics, the photosynthetic pigment contents, the enzyme activities in C3 and C4 pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Previous investigations revealed that the reduction of Chl b is bigger than that of Chl a [28]. Additionally, some studies found an increase in chlorophyll content in Vitis hybrids and in Avena sativa after prolonged growth in water scarcity [29,30]. At the same time, drought has a smaller influence on carotenoid content than chlorophylls.…”
Section: Introductionmentioning
confidence: 95%
“…Previous investigations revealed that the reduction of Chl b is bigger than that of Chl a [28]. Additionally, some studies found an increase in chlorophyll content in Vitis hybrids and in Avena sativa after prolonged growth in water scarcity [29,30]. At the same time, drought has a smaller influence on carotenoid content than chlorophylls.…”
Section: Introductionmentioning
confidence: 95%
“…Drought-tolerant plants have less reduction in water content, higher membrane stability, and photosynthetic activity. RWC is a measure of plant water status, reflecting the metabolic activity in tissues and plants’ capacity for osmotic adjustment [ 51 ], and is used as an index for dehydration tolerance [ 20 , 25 , 52 ]. Its stronger reduction in Fermer plants under moderate stress indicates lower drought tolerance in comparison to Gizda ( Figure 1 a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, carotenoids in higher plants have many roles, including the regulation of light harvesting [ 54 ], ROS-scavenging, and preventing oxidative damage, thereby increasing plant stress tolerance [ 55 ]. The decline in the abundance of photosynthetic pigments could have a negative impact on the effective photosynthetic performance and crop yield [ 51 , 56 ]. A higher Chl and Car content under stress conditions has also been associated with the tolerance of plants, as the decrease in pigment content correlates with decreased RWC [ 20 ], which was demonstrated by our results indicating a higher tolerance of Gizda than Fermer.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh leaves of WT, bhlh1, bhlh2, and bhlh1bhlh2 knockout lines at five weeks of age were stressed with withholding watering for 7 days for measurement of physiological parameters related to drought, including relative water content (RWC), MDA, and H 2 O 2 [50].…”
Section: Measurements Of Physiological Parametersmentioning
confidence: 99%